An in-depth analysis of the English - Vietnamese translation version of Jack London's famous novel The Call of the Wild . M.A Thesis Linguistics : - Nguyễn, Thị Hoàn (University of Languages and International Studies, 2017)
This minor thesis has conducted a comprehensive research and analysis into the translation quality of Chapter 6 – The Call of the Wild by Jack London. The researcher based the analysis on J. House’s model with 8 dimensions elaborated in two categories: Lan (...)